Durable proton exchange membrane and preparation method thereof

Through the structural and morphological regulation of silicon-based modified materials, the problem of poor durability of proton exchange membranes is solved, and the preparation of durable membranes is realized, which enhances oxidation resistance and hydrophilicity, avoids agglomeration and settlement, and improves transmission Quality performance.

CN118878892BActive Publication Date: 2024-12-20JIANGSU YUANHYDROGEN NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411364381.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20
Estimated Expiration
2044-09-29

Smart Images

  • Figure CN118878892B_ABST
    Figure CN118878892B_ABST
Patent Text Reader

Abstract

The invention relates to a proton exchange membrane, and discloses a durable proton exchange membrane and a preparation method thereof. Tetraethyl orthosilicate, ethanol and a modifier or a precursor of the modifier are mixed to form a precursor solution, and hydrochloric acid is added to adjust the pH to form a sol. PS colloidal crystals are immersed in the sol, and the PS colloidal crystals are taken out after filtering and calcined to obtain a three-dimensional porous silicon-based modifier Si / X; Si / X is added to the Nafion solution and stirred at high temperature, and the solution is dried to obtain a preliminarily cured resin; the resin is crushed, Si / X is added, mixed, stirred at high temperature, and rolled to perform secondary curing to obtain a secondary cured resin, and the obtained resin is added to an isopropanol solvent, stirred in a water bath to obtain a casting liquid, and the casting liquid is coated on a PET backing, and dried to obtain a durable proton exchange membrane. The present invention reduces the bulk density and improves the compatibility by regulating the structure and morphology of the silicon-based modified material, so that the oxidation resistance and hydrophilicity of the membrane are enhanced, and the problems of product agglomeration, sedimentation and outflow are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of proton exchange membranes, and in particular to a durable proton exchange membrane and a preparation method thereof. Background Art

[0002] The high cost, poor durability, and short lifespan of perfluorosulfonic acid resin, the main raw material for proton exchange membranes, have always been a pain point for proton exchange membranes. To improve membrane durability and extend lifespan, researchers are focusing on free radical scavengers and water-retaining agents, with the following main directions:

[0003] Free radical scavengers can improve the antioxidant capacity of the membrane and enhance the durability of the membrane. Cerium oxide CeO2 is commonly used. Cerium is a variable valence element. 3+ Easily oxidized to Ce 4+ , and then eliminate oxides such as hydroxyl (HOO•) and (HO•) free radical reactions. Ce 4 + The electrons are reduced to Ce 3+ , CeO2 can be used repeatedly.

[0004] To improve water retention and other properties, inorganic nanoparticles such as SiO2, TiO2, and heteropolyacids are primarily used. These materials have strong hygroscopic properties and can enhance hydrophilicity. Numerous studies have shown that a growing number of modifying substances can enhance membrane performance. These include Pt, Ag2O, Al2O3, ZnO, CaO, ZrO2, Fe2O3, SiC, SBA-15, graphene, and carbon nanotubes.

[0005] A common method involves directly adding the modified nanoparticles (modifiers) to a perfluorosulfonic acid solution, followed by membrane formation. This method has the disadvantage that the modified materials tend to aggregate within the membrane system, blocking mass transfer channels and causing sedimentation and outflow. Sedimentation and agglomeration are physical phenomena, often related to the density difference and affinity between the two phases.

[0006] Proton exchange membranes are primarily a family of perfluorosulfonic acid membranes, such as DuPont's Nafion membranes. The primary mass transfer mechanism in perfluorosulfonic acid membranes is that the groups in the membrane system exist as spherical ion clusters, connected by parallel channels. Protons are transferred between these clusters, and these channels are typically less than 5 nm. If these channels are blocked by rigid modified nanoparticles, proton transfer is impaired. Sedimentation occurs due to density differences. While density is generally understood in physics as absolute density, bulk density is more appropriate for practical production. To avoid sedimentation, the bulk density of the modifier must be adjusted and the process optimized. Summary of the Invention

[0007] The main technical problem solved by the present invention is to provide a durable proton exchange membrane and a preparation method thereof. By regulating the structure and morphology of silicon-based modified materials, the bulk density is reduced, the compatibility is improved, the oxidation resistance and hydrophilicity of the membrane are enhanced, and the problems of agglomeration, sedimentation and outflow during product use are improved.

[0008] In order to solve the above technical problems, a technical solution adopted by the present invention is: to provide a method for preparing a durable proton exchange membrane, comprising the following steps: S1. preparing a three-dimensional porous silicon modifier: mixing tetraethyl orthosilicate, ethanol and a modifier or a modifier precursor to form a precursor solution, adding hydrochloric acid to the precursor solution to adjust the pH to a strong acid and form a sol, immersing PS colloidal crystals in the sol, allowing silicon seeds to grow inside the PS colloidal crystals, filtering and removing the PS colloidal crystals and calcining them to obtain a three-dimensional porous silicon-based modifier, and the three-dimensional porous silicon-based modifier is named Si / X; S2. primary curing: in Naf Si / X is added to the Nafion solution, and the solution is stirred at high temperature so that the Nafion solution is absorbed into the porous structure of Si / X. After the solution is dried, a preliminarily cured resin is obtained; S3. Secondary curing: the resin prepared in S2 is crushed, Si / X is added and mixed, and then stirred at high temperature and rolled for secondary curing to obtain a secondary cured resin, wherein the amount of Si / X is less than that in the primary curing; S4. Preparation of proton exchange membrane: the resin prepared in S3 is added to isopropyl alcohol solvent, stirred in a water bath to obtain a casting solution, the casting solution is coated on a PET backing, and dried to obtain a durable proton exchange membrane.

[0009] In a preferred embodiment of the present invention, the mass ratio of the modifier precursor or modifier, tetraethyl orthosilicate, and ethanol in S1 is 1:2-34:4-45.

[0010] In a preferred embodiment of the present invention, the modifier precursor is cerium nitrate, and the modifier is titanium oxide, zirconium oxide or aluminum oxide.

[0011] In a preferred embodiment of the present invention, the mass fraction of Si / X in the preliminarily cured resin in S2 is 0.5-5%.

[0012] In a preferred embodiment of the present invention, the amount of Si / X in S3 is 20% of the amount of Si / X in primary curing.

[0013] In a preferred embodiment of the present invention, Si / X obtained from modified precursors of different masses are Si / CeO2-1, Si / CeO2-0.5, and Si / CeO2-5, and Si / X obtained from modified precursors of different masses and raw materials are Si / TiO2-1, Si / Al2O3-1, and Si / HSW-1.

[0014] In a preferred embodiment of the present invention, the resin content of the casting solution in S4 is 10-12%.

[0015] In a preferred embodiment of the present invention, the stirring temperature in S2 is 60-80°C, the stirring time is 3-5h, and the drying temperature is 120-140°C.

[0016] In a preferred embodiment of the present invention, the temperature of the stirring and rolling in S3 is 120-150° C., and the stirring and rolling are performed at least twice.

[0017] The beneficial effects of the present invention are as follows: the durable proton exchange membrane and the preparation method thereof of the present invention are used to prepare the modified porous material Si / X. By regulating the structure and morphology of the silicon-based modified material, the Si / X has a three-dimensional ordered structure, is light in weight, and has a large specific surface area. Ion clusters are distributed and interspersed in the three-dimensional pore structure of the porous material, which does not affect the mass transfer of protons, and makes the contact area between the two phases larger, the van der Waals force and the electrostatic force between molecules stronger, reduces agglomeration, reduces the bulk density, improves compatibility, enhances the membrane's antioxidant properties and hydrophilicity, and improves problems such as agglomeration, sedimentation, and outflow during product use.

[0018] The durable proton exchange membrane and preparation method of the present invention adopt a graded solidification method to dope the modified substance, changing the conventional method of adding the modified substance to the casting solution, allowing the ion cluster structure that plays a mass transfer role to fully contact the modified material, further improving performance and reducing outflow. It does not require a preparation process under harsh conditions and is highly practical. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive work, among which:

[0020] Figure 1 is an electron microscope image of Si / CeO2-1 of Example 1;

[0021] Figure 2 These are the infrared characterization test results of Si / CeO2-1 and silicon oxide in Example 1;

[0022] Figure 3 These are the infrared characterization test results of Si / CeO2-1 after different time periods in Example 1. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention will be described clearly and completely below. The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so that people familiar with this technology can understand and read them. They are not used to limit the limiting conditions for the implementation of the present invention, so they have no technical substantive significance. Any modification of the structure, change in the proportional relationship, or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the efficacy and purpose that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and so on quoted in this specification are only for the convenience of description, and are not used to limit the scope of implementation. Changes or adjustments in their relative relationships should also be regarded as the scope of implementation of the present invention without substantially changing the technical content.

[0024] In Example 1, 18g of ethanol, 25g of TEOS (tetraethyl orthosilicate), and 3.4g of cerium nitrate (cerium nitrate: tetraethyl orthosilicate: ethanol = 1:7.35:5.29) were weighed and dissolved in a water bath at 50°C. 1.2g of hydrochloric acid and 1.1g of distilled water were added to adjust the pH to approximately 1. A polystyrene (PS) colloidal crystal was slowly placed into the solution until just submerged. The vacuum flask was maintained at a negative pressure of <-0.08MPa and allowed to stand for 4-5 hours. The PS colloidal crystal was removed and calcined in a muffle furnace at 400°C for 10 hours at a heating rate of 1°C / min. A modifier, Si / CeO2-1 (1 represents the resin ratio), was prepared, with a cerium oxide loading of 20%.

[0025] Take 100g of 25% Nafion solution, add 0.3g of Si / CeO2-1, stir at 60℃ for 4h, and then perform primary curing in an oven at 120℃ until evaporated to dryness. The content of Si / CeO2-1 in the resin is 1%.

[0026] The aforementioned dry resin was chopped up, and 0.06 g of Si / CeO2-1 was added. The mixture was stirred and rolled twice at 150°C to complete secondary curing to obtain a resin.

[0027] The above resin was dissolved in isopropyl alcohol solvent to prepare a new solution with a resin content of 10%, and stirred in a 40°C water bath for 28 hours to obtain a casting solution.

[0028] Lay a PET backing flat on a blade coater, adjust the blade spacing to 60°C, and start the vacuum pump (vacuum degree <-0.08 MPa). Once the temperature reaches the desired level, set the blade speed to 5 mm / s, evenly apply the casting solution to the PET backing, and start the blade coater. Once the membrane is dry, remove it and place it in a drying oven, first at 100°C for 2 hours and then at 120°C for 2 hours to prepare the proton exchange membrane.

[0029] In Example 2, 30 g of ethanol, 25 g of TEOS, and 0.74 g of cerium nitrate were weighed and dissolved in a water bath at 50 ° C with stirring. 1.2 g of hydrochloric acid and 1.1 g of distilled water were added to adjust the pH to about 1. A PS colloidal crystal was slowly placed in the above solution until the solution was just immersed. As for the vacuum bottle, the negative pressure was maintained at <-0.08 MPa and allowed to stand for 4 to 5 hours. The PS colloidal crystal was taken out and placed in a muffle furnace and calcined at 400 ° C for 10 hours with a heating rate of 1 ° C / min. A modifier Si / CeO2-0.5 (0.5 represents the resin ratio) was prepared, in which the cerium oxide loading was 5%.

[0030] Take 100g of 25% Nafion solution, add 0.14g of Si / CeO2-0.5, stir at 70℃ for 3h, and then perform primary curing in an oven at 130℃ until evaporated to dryness. The content of Si / CeO2-0.5 in the resin is 0.5%.

[0031] The aforementioned dry resin was chopped up, and 0.028 g of Si / CeO2-1 was added. The mixture was stirred and rolled twice at 130°C to complete secondary curing to obtain a resin.

[0032] The above resin was dissolved in isopropyl alcohol solvent to prepare a new solution with a resin content of 11%, and stirred in a water bath at 40°C for 28 hours to obtain a casting solution.

[0033] Lay a PET backing flat on a blade coater, adjust the blade spacing to 60°C, and start the vacuum pump (vacuum degree <-0.08 MPa). Once the temperature reaches the desired level, set the blade speed to 5 mm / s, evenly apply the casting solution to the PET backing, and start the blade coater. Once the membrane is dry, remove it and place it in a drying oven, first at 100°C for 2 hours and then at 120°C for 2 hours to prepare the proton exchange membrane.

[0034] In Example 3, 15 g of ethanol, 10 g of TEOS, and 3.6 g of cerium nitrate were weighed and dissolved in a water bath at 50°C with stirring. 1.2 g of hydrochloric acid and 1.1 g of distilled water were added to adjust the pH to about 1. A PS colloidal crystal was slowly placed in the above solution until the solution was just immersed. As for the vacuum bottle, the negative pressure was maintained at <-0.08 MPa and allowed to stand for 4 to 5 hours. The PS colloidal crystal was taken out and placed in a muffle furnace and calcined at 400°C for 10 hours with a heating rate of 1°C / min. A modifier Si / CeO2-5 (5 represents the resin ratio) was prepared, in which the cerium oxide loading was 5%.

[0035] Take 100g of 25% Nafion solution, add 1.4g of Si / CeO2-0.5, stir at 80℃ for 5h, and then perform primary curing in an oven at 140℃ until evaporated to dryness. The content of Si / CeO2-5 in the resin is 5%.

[0036] The aforementioned dry resin was chopped up, and 0.28 g of Si / CeO2-1 was added. The mixture was stirred and roller pressed twice at a temperature of 120°C to complete secondary curing to obtain a resin.

[0037] The above resin was dissolved in isopropyl alcohol solvent to prepare a new solution with a resin content of 12%, and stirred in a 40°C water bath for 28 hours to obtain a casting solution.

[0038] Lay a PET backing flat on a blade coater, adjust the blade spacing to 60°C, and start the vacuum pump (vacuum degree <-0.08 MPa). Once the temperature reaches the desired level, set the blade speed to 5 mm / s, evenly apply the casting solution to the PET backing, and start the blade coater. Once the membrane is dry, remove it and place it in a drying oven, first at 100°C for 2 hours and then at 120°C for 2 hours to prepare the proton exchange membrane.

[0039] In Examples 4-6, silicon-based modifiers were prepared using different modifiers according to the method and incorporation ratio of Example 1.

[0040] In Example 4, 1 g of titanium oxide, 2 g of TEOS, and 4 g of ethanol were used, and the rest was the same as in Example 1.

[0041] In Example 5, 1 g of aluminum oxide, 10 g of TEOS, and 20 g of ethanol were used, and the rest was the same as in Example 2.

[0042] In Example 6, 1 g of silicotungstic acid, 34 g of TEOS, and 45 g of ethanol were used, and the rest was the same as in Example 3.

[0043] The characteristics and relevant test data of each embodiment are summarized in the following table:

[0044] Modified substance or modified substance precursor name Incorporation amount / % <![CDATA[Bulk density ρb / kg / m 3 > Example 1 Cerium nitrate <![CDATA[Si / CeO2-1]]> 1 1.171 Example 2 Cerium nitrate <![CDATA[Si / CeO2-0.5]]> 0.5 1.131 Example 3 Cerium nitrate <![CDATA[Si / CeO2-5]]> 5 1.236 Example 4 titanium oxide <![CDATA[Si / TiO2-1]]> 1 1.167 Example 5 Alumina <![CDATA[Si / Al2O3-1]]> 1 1.142 Example 6 Silicotungstic acid Si / HSW-1 1 1.160

[0045] In a comparative example, the Nafion solution was reconstituted with isopropyl alcohol to a resin mass fraction of 10%, and a proton exchange membrane was prepared by direct coating under the same conditions as in Example 1.

[0046] The Si / CeO2-1 in Example 1 was subjected to SEM testing to characterize its porous structure;

[0047] Since the content of heteropolyacid in the proton membrane is low and there is much interference in infrared detection, the infrared characterization effects of Si / CeO2-1 and SiO2 in Example 1 were taken;

[0048] Si / CeO2-1 was soaked in aqueous solution, and samples were taken after soaking for 0h, 24h, 72h, and 120h, and then dried and subjected to infrared testing;

[0049] The proton exchange membrane prepared in Example 1 was immersed in deionized water, and the changes in water conductivity and pH were measured for one month.

[0050] The thickness and conductivity of the proton exchange membranes in the examples and comparative examples were tested at different temperatures and humidities.

[0051] Test results: SEM test was performed on Si / CeO2-1 of Example 1. Figure 1 .

[0052] Infrared characterization results: load and loss, such as Figure 2 .

[0053] The Si / CeO2-1 of Example 1 was tested by infrared spectroscopy. -1 ~1000cm -1 The characteristic peak of Si-O-Si bond becomes broader, which is the effect of CeO2 loaded on SiO2.

[0054] The above Si / CeO2-1 was immersed in deionized water and kept at room temperature of 25℃. The samples were dried and tested by infrared spectroscopy after 10 days and 30 days respectively. The results showed that 900 -1 ~1000cm -1 There are still characteristic peaks at the bottom, indicating that CeO2 in the sample is loaded on SiO2 and no obvious loss occurs.

[0055] Supplementary results of the bleed test: During the sample testing phase of Example 1, the proton membrane prepared in different time intervals was immersed in a deionized water solution, maintained at room temperature of 25°C, and water samples were taken at different immersion periods for pH and conductivity.

[0056] Example 1 Conductivity / μs / cm pH pure water 12.22 6.98 1 day 12.25 7.02 2 days 12.22 7.05 3 days 12.26 6.99 4 days 12.26 7.02 5 days 12.25 7.06 10 days 12.24 7.02 15 days 12.25 7.02 20 days 12.29 7.02 25 days 12.27 7.04 30 days 12. 38 7.04

[0057] There were no significant changes in conductivity and pH, no acidic substances flowed into the solution, and no obvious outflow phenomenon occurred.

[0058] Proton membrane thickness, tensile strength, and conductivity test results: Conductivity was tested at low humidity of 23% and 80°C.

[0059] Testing has shown that the addition of modifiers to the Examples improves membrane conductivity at low humidity compared to the Comparative Examples. Examples 1-3 show that increasing the proportion of silicon-based modifiers also increases conductivity. The average thickness of the prepared perfluorosulfonic acid proton membranes is approximately 11 μm.

[0060] The present invention combines physical and chemical perspectives to achieve improvements, finding out the root cause of sedimentation from a physical perspective and constructing a two-phase effect of a modifier and a membrane system from a chemical perspective.

[0061] The present invention uses commercially available Nafion as raw material, reduces the resin content, prepares perfluorosulfonic acid membranes, and reduces membrane production costs. A porous silicon-based modifier is added to enhance the membrane's antioxidant and water retention properties. The porous structure of the modifier is utilized, and the resin is maintained at a high temperature to form a mobile phase, allowing the modifier and resin to be fully mixed, thereby avoiding agglomeration and clogging of mass transfer channels. A graded curing method is introduced into the membrane formation process to strengthen the bond between the modifier and the membrane system and prevent outflow. Multiple test results indicate that the modified proton exchange membrane has enhanced performance.

[0062] The durable proton exchange membrane produced by the present invention reduces resin content while adding a silicon-based modifier to improve the membrane's mass transfer and hydrophilicity. Controlling the structure and morphology of the modifier is key to improving performance and can avoid sedimentation problems associated with traditional modification methods. A graded curing method is introduced into the membrane formation process to prevent the modifier from being released outside the membrane system and reduce outflow. The fixation of the modifier by silicon oxide was characterized using various modern analytical techniques, including SEM and infrared. No significant outflow of the modifier was observed during outflow testing.

[0063] The above is a schematic description of the present invention and its embodiments, which is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by this and, without departing from the purpose of the present invention, designs a structure and embodiment similar to this technical solution without inventiveness, they shall fall within the scope of protection of the present invention.

Claims

1. A method for preparing a durable proton exchange membrane, characterized in that: The following steps are involved: S1. Preparing a three-dimensional porous silicon modifier: mixing tetraethyl orthosilicate, ethanol and a modifier to form a precursor solution, or mixing tetraethyl orthosilicate, ethanol and a precursor of the modifier to form a precursor solution, The precursor of the modified substance is cerium nitrate, and the modified substance is titanium oxide, zirconium oxide, aluminum oxide or tungsten silicate. Hydrochloric acid is added to the precursor solution to adjust the pH to a strong acid and form a sol, and the PS colloidal crystal is immersed in the sol to allow the silicon seed to grow inside the PS colloidal crystal. The PS colloidal crystal is taken out after filtering and calcined to obtain a three-dimensional porous silicon-based modifier, i.e., a silicon-modified product, and the three-dimensional porous silicon-based modifier is named Si / X; S2. Primary curing: Si / X is added to the Nafion solution, and the solution is stirred at high temperature so that the Nafion solution is absorbed into the porous structure of Si / X. The solution is dried to obtain a preliminarily cured resin. The mass fraction of Si / X in the preliminarily cured resin in S2 is 0.5-5%; S3. Secondary curing: The resin prepared in S2 is crushed, Si / X is added, mixed, stirred at high temperature, and rolled for secondary curing to obtain a secondary cured resin, wherein the amount of Si / X is less than the amount of Si / X in the primary curing, and the amount of Si / X in S3 is 20% of the amount of Si / X in the primary curing; S4. Preparation of proton exchange membrane: Add isopropanol solvent to the resin prepared in S3, stir in a water bath to obtain a casting solution, apply the casting solution on a PET backing, and dry to obtain a durable proton exchange membrane.

2. The method for preparing a durable proton exchange membrane according to claim 1, characterized in that: The mass ratio of the modified substance precursor or modified substance, tetraethyl orthosilicate, and ethanol in S1 is 1:2-34:4-45.

3. The method for preparing a durable proton exchange membrane according to claim 1, characterized in that: The resin content of the casting solution in S4 is 10-12%.

4. The method for preparing a durable proton exchange membrane according to claim 1, characterized in that: In S2, the stirring temperature is 60-80°C, the stirring time is 3-5h, and the drying temperature is 120-140°C.

5. The method for preparing a durable proton exchange membrane according to claim 1, characterized in that: The temperature of stirring and rolling in S3 is 120-150° C., and the number of stirring and rolling is at least 2 times.

6. A durable proton exchange membrane, characterized in that: The durable proton exchange membrane is prepared by the method for preparing the durable proton exchange membrane according to claim 1.